PENGARUH PEMBIAYAAN MURABAHAH TERHADAP PROFITABILITAS PADA BANK SYARIAH DI INDONESIA - Selviana, Sella; Gunaepi , Aang; Muti , Ahmad (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
In buying and selling transactions, it is not uncommon for the public to make cash payments. Therefore, one of the solutions that can be taken to meet their needs is by making purchases in installments or through financing. The financing provided by the bank is a murabahah lil ‘amil bisyiro contract. This study aims to determine and analyze the impact and the extent of the influence of murabahah financing on the profitability (ROA) of Islamic banks in Indonesia. This study uses a quantitative method with secondary data obtained through the official website of the Financial Services Authority. The data is analyzed using simple linear regression analysis and classical assumption tests first. The research results show that murabahah financing has a significant negative impact on bank profitability within the scope of Return On Assets. With a significant value obtained of less than 5% and a t-test result of -2.891 compared to the t-table of 1.657, as well as an influence magnitude on R Square in the range of 6%, it is found that the tested variable is considered to have a low influence.